The Role Of Chronic Norovirus Infection In The Enteropathy Associated With Common Variable Immunodeficiency. (February 2015) - Woodward, Jeremy M; Gkrania‐Klotsas, Effrossyni; Cordero‐Ng, Anthony YK; Aravinthan, Aloysious; Bandoh, Betty N; Liu, Hongxiang; Davies, Susan; Zhang, Hongyi; Stevenson, Philip; Curran, Martin D; Kumararatne, Dinakantha
Abstract : OBJECTIVES: A severe enteropathy of unknown etiology can be associated with common variable immunodeficiency (CVID). METHODS: Stool and archived small intestinal mucosal biopsies from patients with CVID enteropathy were analyzed by PCR for the presence of Norovirus RNA. The PCR products were sequenced to determine the relationship of viral isolates. Stool samples from 10 patients with CVID but no enteropathy served as controls. RESULTS: All eight patients in our CVID cohort with enteropathy showed persistent fecal excretion of Norovirus. Analysis of archived duodenal biopsies revealed a strong association between the presence of Norovirus and villous atrophy over a period of up to 8 years. Analysis of the viral isolates from each patient revealed distinct strains of genogroup II.4. Sequence analysis from consecutive biopsy specimens of one patient demonstrated persistence of the same viral strain over a 6‐year period. CVID patients without enteropathy showed no evidence of Norovirus carriage. Viral clearance occurred spontaneously in one patient and followed oral Ribavirin therapy in two further patients, and resulted in complete symptomatic and histological recovery. However, Ribavirin treatment in two further patients was unsuccessful. CONCLUSIONS: Norovirus is an important pathogen for patients with CVID and a cause of CVID enteropathy, as viral clearance, symptom resolution, and histological recovery coincide. Ribavirin requires further evaluation as a potential therapy.